(untitled) (Research, Society and Development, 2022)
Objective: to map the scientific publications on the use of music therapy for patients with Covid-19. Method: this is a scoping review developed according to the Joanna Briggs Institute methodology. The search was conducted in the Virtual Health Library, PubMed, Web of Science, Scopus, EMBASE, as well as in non-indexed national and international journals specific to music therapy. Articles published until March 2022 that addressed music therapy or music intervention for therapeutic purposes in the care of patients diagnosed with Covid-19 were included. The summarization of the results occurred descriptively by means of tables and qualitative analysis of the contents of the text of each article. Results: the sample consisted of five publications ranging from original articles such as experimental studies to case reports of clinicians, which were synthesized into three categories, namely: 1. Music without boundaries for patients with Covid-19, 2. Music experiences and music therapy methods adopted in the care of patients with Covid-19, 3. Effects of music therapy/music intervention on patients with Covid-19 and their caregivers. Conclusion: despite the scarcity of studies on the subject, it is concluded that music therapy has been used mainly in the online modality, crossing physical barriers to reach the home or the bed of patients with Covid-19, from the use of different musical experiences and music therapy methods that contribute to the improvement of vital parameters, decreased anxiety, improved quality of life, and reduced isolation and stimulation of social connection between patients with Covid-19 and their families/caregivers.